Zero-grade denominative nasal and sta-presents in Baltic - Villanueva Svensson, Miguel (Baltistica, 2016)
The article deals with relics of zero-grade fientive denominative nasal and sta-presents in Baltic even when derived from full-grade nominals, a derivational pattern going back to "Northern Indo-European".
Keywords: Baltic; Indo-European; historical morphology; verb; denominative; ablaut